Lasing of N+2induced by filamentation in air as a probe for femtosecond coherent anti-Stokes Raman scattering - Zhao, Xiaodong; Nolte, Stefan; Ackermann, Roland (Optics Letters, 2020)
We investigated ultrashort pulse filamentation and lasing action of N+2 for pump-probe experiments in gases. Using femtosecond coherent anti-Stokes Raman scattering, the white-light supercontinuum generated in the filament was used to excite ro-vibrational Raman transitions in air, CO2 and CH4. We show that the lasing pulse acts as a probe for the excited levels by detecting the corresponding anti-Stokes Raman spectroscopy signals. This feature may be applied to remote sensing applications, as the temporal and spatial alignment of the probe beam and the filament is intrinsically provided.
CRIS-Team Scopus Importer:2023-04-20